2023
DOI: 10.3390/jcm12227080
|View full text |Cite
|
Sign up to set email alerts
|

A Manifesto in Defense of Pain Complexity: A Critical Review of Essential Insights in Pain Neuroscience

Javier Picañol Párraga,
Aida Castellanos

Abstract: Chronic pain has increasingly become a significant health challenge, not just as a symptomatic manifestation but also as a pathological condition with profound socioeconomic implications. Despite the expansion of medical interventions, the prevalence of chronic pain remains remarkably persistent, prompting a turn towards non-pharmacological treatments, such as therapeutic education, exercise, and cognitive-behavioral therapy. With the advent of cognitive neuroscience, pain is often presented as a primary outpu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 162 publications
0
3
0
1
Order By: Relevance
“…Despite such uniformity, the final output may reflect a net reduction in the capacity to exert force ( 82 ). On the other hand, pain as a complex experience entails affective-motivational aspects capable of affecting more complex constructs of the individual ( 83 , 84 ). In the effort to alleviate nociceptive pain, several studies have demonstrated how techniques such as not only electrical stimulation but also botulinum toxin injections lead to a reduction in symptoms along with an improvement in joint function ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite such uniformity, the final output may reflect a net reduction in the capacity to exert force ( 82 ). On the other hand, pain as a complex experience entails affective-motivational aspects capable of affecting more complex constructs of the individual ( 83 , 84 ). In the effort to alleviate nociceptive pain, several studies have demonstrated how techniques such as not only electrical stimulation but also botulinum toxin injections lead to a reduction in symptoms along with an improvement in joint function ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recientemente se ha cuestionado el supuesto papel cerebro-céntrico para el caso del dolor persistente, debido al rol fundamental que también juega en la cronificación del dolor no solo el sistema nervioso periférico, sino incluso otros factores más allá del propio sistema nervioso (Párraga, 2023). El concepto de dolor nociplástico, además, parece sugerir que es razonable postular que un proceso que puede estar asociado con el dolor se ha activado de otra manera que no sea a través de nociceptores: de ahí la inferencia de "nocicepción alterada" o "función nociceptiva alterada" (Cohen et al, 2023).…”
Section: ¿Y Si El Dolor Crónico Tiene Más Que Ver Con Las Perturbacio...unclassified
“…Pain after bodily injury is often accompanied by complex behavioral and neural alterations that are poorly understood 12, 58 , and may cause clinical problems long after surgery or trauma 28, 37,59 . Ongoing behavioral effects manifested acutely after significant tissue injury include spontaneous grimacing, guarding behavior, and reduced locomotor activity 12, 60, 67, 73 , while a prominent ongoing neural effect is spontaneous electrical activity in primary afferent neurons 10, 25, 39, 62, 75 .…”
Section: Introductionmentioning
confidence: 99%